Implementing Hierarchical Role-Based Access Control for Document Administration in Student Organizations - Destini, Janessa Sarah; Tony, Tony (Internet of Things and Artificial Intelligence Journal, 2024)
Student organizations in higher education institutions play a pivotal role in fostering leadership and collaboration. Despite their importance, many still utilize manual document administration processes, resulting in inefficiencies, delays, and a lack of transparency. This research introduces the design and implementation of a web-based Document Management System integrated with Hierarchical Role-Based Access Control (HRBAC) for student organizations at Universitas Tarumanagara. The system adopts a structured and secure framework tailored to the organization’s approval hierarchy, encompassing roles such as UKM/HIMA, BEM, DPM, Faculty Advisors, Deans, and the Student Affairs Office. Each role is assigned specific access privileges to ensure secure and efficient document submission and approval workflows, aligned with organizational needs. The system was developed using the Laravel framework, PHP, HTML, SCSS, JavaScript, and MySQL, following the Waterfall methodology. Usability was evaluated using the System Usability Scale (SUS), achieving a score of 78.33, categorizing it as “Good” in terms of user experience and navigability. The findings indicate significant improvements in process automation, role-based access control, and document traceability. This research offers a comprehensive model for digital transformation in student organization administration, emphasizing the effectiveness of hierarchical access control in optimizing administrative workflows within academic institutions.